Program Brain Breaks Berbasis Aktivitas Fisik untuk Peningkatan Fungsi Kognitif Siswa SD Inpres Kera-Kera Kota Makassar - Abdullah, Meutiah Mutmainnah; Nuskin, Gita Safirah; Purnamasari, Nahdiah; Ahsaniyah, Andi Besse; Harisa, Akbar; Hamisah, Hamisah; Gondo, Adi Ahmad; Hasyar, Andi Rizky Arbaim; Aras, Djohan; Permana, Andi Fajrin; Fitriani, Nurlaila (Universitas Baiturrahim, 2024)
The Brain-breaks program is presented as a program designed to improve children's motor and cognitive abilities. This program presents movements that will improve neuroplasticity mechanisms in order to improve short-term memory and attention skills in a fun and easy to follow way. The aim of this community service activity is that participants can carry out physical training movements in the form of motor and cognitive exercises which can then be assessed on cognitive function. A total of 21 students from SD Inpres Kera-Kera participated in this activity. Activity participants showed satisfactory results in memory and attention abilities after giving the Brain-Breaks program through measuring the digit span test which showed an increase in 14 students, measuring the Stroop test where there was an increase in the word test from 85.7% before giving the program to reach 100 % after giving the program followed by the color test from 62% to 90.4%, and the color-word test score from 4.76% to 23.8%, as well as the distribution of knowledge and mastery of the brain-breaks program material which increased from 0% to 100% after giving the program, apart from that, participants have also been able to practice the types of games that have been given with the help of the class teacher or done independently. Based on the results and discussion, it is known that the brain breaks program can improve short-term memory and attention in an effort to improve the cognitive quality of students at Inpres Kera-Kera Elementary School, Makassar City.